PENGARUH MALOKLUSI KELAS II DIVISI 1 TERHADAP KEJELASAN PENGUCAPAN FONEM VOKAL (/o/,/u/), FONEM KONSONAN BILABIAL (/p/,/b/,/m/), FONEM KONSONAN LABIODENTAL (/f/) DAN DALAM BENTUK MORFEM (kajian pada anak perempuan usia 12 tahun) - , ennita rakhmawaty, drg. Rinaldi Budi Utomo, MS., Sp.KGA(K). ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Class II division 1 malocclusion can cause a variety of problems one of which is the problem of pronunciation. Pronunciation can be interrupted if there is a change in the composition of the teeth. This study aims to determine the effect of class II division 1 malocclusion on the clarity of pronunciation of vowel phonemes (/ o /, / u /), bilabial consonant phonemes (/ p /, / b /, / m /), consonants labiodental (/ f /) and in the form of a morpheme in terms of the frequency of the sound. The study was conducted on 20 girls aged 12 years at SDN Perumnas Depok Sleman Yogyakarata. The subjects consisted of two groups: normal group (10 children) and group II division 1 malocclusion class (10 children). Voice recording is done in room closed closed by using a tape recorder. Voice recording is done when the subjects pronounce vowel phonemes (/ o /, / u /), bilabial consonant phonemes (/ p /, / b /, / m /), labiodental consonant phonemes (/ f /) and in the form of a morpheme is the pompa, bumi, mumi, fobi, obi, umbi. Frequency values obtained by analyzing the results of the sound recording using Cool Edit software .Data were tested by t-test Independent. The results showed that there were differences in the mean value of the frequency in the normal group, namely the phoneme / p / 368.20, the phoneme / b / 513.27, the phoneme / m / 564.62, the phoneme / f / 392.72, the phoneme / o / 480.28, the phoneme / u / 547.16, pompa 280.44, bumi 357.21, mumi 487.77, fobi 286.01, obi 346.40, 466.10 umbi while the class II division 1 malocclusion is the phoneme / p / 362.48, the phoneme / b / 508.40, the phoneme / m / 558.69, the phoneme / f / 388.01, the phoneme / o / 476.16, the phoneme / u / 544.25, pompa 278.14, bumi 353.81, mumi 484.36, fobi 281.90 , obi 344.85, umbi 463.13. In the independent t-test results of phoneme and morpheme test showed a significant difference (P <0.05) between the normal group and the group with Class II division 1. Conclusion The results of the study with Class II division 1 can reduce the clarity of the pronunciation of the vowel phoneme / o /, / u /, bilabial consonant phonemes / p /, / b /, / m /, labiodental consonant phonemes / f /, and in the form of a morpheme is the pompa, bumi, mumi, fobi, obi, umbi.